ANALYSIS OF ISOTOPE Cs ON PROCESSING SEPARATION OF Cs AND ZEOLITE USING SPECTROMETRY-Î³ - Arif Nugroho; Dian Anggraini; Noviarty Noviarty (Institut Teknologi Bandung, 2010)
The analysis of Cs-isotope was conducted on separation process of Cs 137 isotope using a Lampung zeolite. Analysis of Cs based on modification of ASTM E320-79 method. Modification process including a Cs separation by extraction using a TBP/OK and by direct sedimentation as CsClO4, which was subsequently applied using a zeolite. Cs-isotope measurement was conducted using spectrometer Î³. The result of Cs 137 analysis through the direct sedimentation with zeolite obtained about 86,40% ± 0,1%, while the analysis of Cs-137 by extraction modification separated process which followed by catching zeolite obtained a recovery about 28,05% ± 5,28%, and by modification precipation process with ASM obtained a recovery about 52,55% ± 1,11%.